Developments in Russian politics - Lankina, Tomila; Hale, Henry E. 1966-; Johnson, Juliet 1968- (Developments in politics, 2024)
"The 10th edition of this go-to-text offers critical discussion of contemporary Russian politics and its fundamental principles. It covers established topics such as executive leadership, parties and elections, and also newer issues of national identity, protest, and Russia and Greater Eurasia. Taking a bottom-up approach, Developments in Russian Politics analyses the political system in which Putin's influence can be understood and covers frequently overlooked topics like informal economy, climate change, and gender"-- Provided by publisher.